IMPLEMENTASI MODEL PROTOTIPE DALAM PEMBUATAN SISTEM INFORMASI PENJUALAN SPAREPART - Yoki Firmansyah; Reza Maulana; Dessy Oktavia Hutagalung (Jurnal Sistem Informasi Akuntansi, 2021)
The prototype model is a model that can be used to design and create information systems, where this model is a rapid development and testing of a working model (prototype) of a new information system through a process of interaction and repetition, there are several stages in the first prototype model. listening to customers, building and refining mockups and viewing and testing mockups. In this paper, the information system that will be built using a prototype model is an information system for the sale of spare parts on the PD. Varia Motor. Where based on observations and interviews with ordering the purchase of spare parts still using conventional methods and causing several problems such as a long time in service to customers, by utilizing a prototype model we can create an information system that can solve these problems, and can improve spare parts sales services at PD. Varia motor